2008
DOI: 10.1017/s1742170507002001
|View full text |Cite
|
Sign up to set email alerts
|

Soil nutrient and plant responses to solarization in an agroecosystem utilizing an organic nutrient source

Abstract: Soil solarization is used to manage nematodes, pathogens and weeds, but relatively few studies have examined solarization effects on soil mineral nutrients, soil properties and plant tissue nutrients. This study was designed to optimize the duration of solarization treatment for the management of soil and plant nutrients and crop biomass in an agroecosystem utilizing an organic nutrient source. The experiment was a split-plot with treatment duration as the main effect and solarization as the sub-effect. Solari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Following solarization, beneficial predators start to return by the end of the next growing season, whereas fumigation has longer-lasting effects (Wang et al 2006). However, Ozores-Hampton et al (2004) and Seman-Varner et al (2008) showed that organic matter decomposition was not affected by solarization, so presumably the beneficial bacteria and fungi involved in decomposition recover quickly after solarization (also see the section below on soil nutrients).…”
Section: Solarization -How Does It Work?mentioning
confidence: 99%
See 1 more Smart Citation
“…Following solarization, beneficial predators start to return by the end of the next growing season, whereas fumigation has longer-lasting effects (Wang et al 2006). However, Ozores-Hampton et al (2004) and Seman-Varner et al (2008) showed that organic matter decomposition was not affected by solarization, so presumably the beneficial bacteria and fungi involved in decomposition recover quickly after solarization (also see the section below on soil nutrients).…”
Section: Solarization -How Does It Work?mentioning
confidence: 99%
“…Solarization coupled with compost increased soil nutrient levels more than treatments with methyl bromide or solarization alone, both of which were combined with inorganic fertilizer. Seman-Varner et al (2008) measured nutrient concentration in the soil and plant tissue of an okra crop following different durations of solarization. While soil potassium (K) and manganese (Mn) were higher following solarization, Copper (Cu) and zinc (Zn) were lower.…”
Section: Soil Nutrientsmentioning
confidence: 99%
“…As an environmentally friendly farming method, soil solarization (SS) uses nature's inexhaustible source of solar energy to disinfest soil-borne plant pathogens and remove weeds without using chemicals, and is also reported to improve plant growth, a phenomenon known as the increased growth response (IGR) (11). The SS-induced IGR has been reported in numerous field trials with various types of soils including silty clay and sandy loam, and with a broad range of crops such as tomato, eggplant, Chinese cabbage, and okra (11)(12)(13)(14)(15)(16)(17); therefore, SS can be a widely applicable agricultural crop production method (18,19). Several hypotheses for the mechanisms explaining the SS-induced IGR have been proposed to date, such as changes in macro-and microelements in the soil such as nitrogen-containing compounds and several minerals, the elimination of minor pathogens, the release of growth regulator-like substances, and the stimulation of beneficial microorganisms.…”
Section: Significancementioning
confidence: 99%
“…(D) Incorporation of dual-labeled alanine into shoot tissue analyzed by LC-MS. (E) The 13 C-labeled compounds (i.e., alanine, succinic acid, glutamine, and proline) metabolized from the absorbed alanine detected by NMR. Deducible 13 C-13 C bondomers are indicated by red lines, and unconfirmed positions of 13 C label are indicated by black dots. (F) Accumulation of 14 C in the shoot traced with labeled alanine.…”
mentioning
confidence: 99%
“…It was reported that solarization is effective against nematode populations up to 20 cm soil depth, solarization + fumigant application is effective up to 35 cm soil depth, when only solarization is applied, the nematodes can survive under 20 cm soil depth and move upwards over time to reach the depth where they can cause economic damages (McSorley et al, 1999). It was reported that solarization applied field plants grow better compared to those of solarization is not applied (McSorley et al, 1999, Seman-Varner et al, 2008. Using metam-sodium or potassium, which are wide spectrum fumigants in vegetables, exhibit diverse results against root-knot nematodes (Desaeger and Csinos, 2006;Zasada et al, 2010).…”
mentioning
confidence: 99%